Preparation of Ag/Au Bimetallic Nanodecahedra through Galvanic Displacement Method - Nga, Pham Thi; Thu Ha, Pham Thi; Dien, Nguyen Dac; Anh, Doan Thi Thao; Trang, Tran Thu; Tuyet, Nguyen Vu Anh; Truong Xuan, Vuong; Xuan Hoa, Vu (VNU Journal of Science: Mathematics - Physics; Vol 41 No 1DO - 10.25073/2588-1124/vnumap.4972, 2025)
In this work, Ag/Au bimetallic nanodecahedra was successfully synthesized using the reduction process and photochemical method. Polyvinylpyrrolidone was used as a shape-directing agent, AgNO 3 , HAuCl 4 as precursor raw materials, sodium borohydride as a reducing agent for the growth of Ag metal. Ag + ions were reduced to Ag nanoparticles (AgNPs) as seeds using sodium borohydride (NaBH 4 ), and then Ag nanodecahedra (AgND) were prepared by a photochemical seeding growth method under the illumination of blue light emitting diode (BLED) with a wavelength of 480 nm. Next, an Au nanofilm was formed by chemical reduction on the surface of the Ag nanodecahedra from precursors of HAuCl 4 and ascorbic acid (C 6 H 8 O 6 ). At the same time, Ag was replaced by Au through a galvanic replacement reaction. As-prepared products have been characterized by X-ray diffraction, scanning electron microscope (SEM), transmission electron microscope (TEM), high-resolution transmission electron microscope (HRTEM), energy dispersive X-ray spectroscopy (EDS), EDX mapping, and ultraviolet-visible (UV-Vis) absorption spectroscopy. The intensity and position of UV-Vis peaks of AgND and Ag/Au changed as BLED illumination time and HAuCl4 amount changed. Keywords : Au/Ag bimetallic, galvanic replacement reaction, nanodecahedra, photochemical reduction.